Rede de Cooperação entre Autores que Publicam nas Temáticas Stakeholders, Agro e Bioenergia, Biocombustíveis e Sustentabilidade - Simone Sehnem (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2013)
This article has aimed to conduct a study of sociometric cooperation between authors about the thematic stakeholders, agriculture and bioenergy, biofuels and sustainability. To operationalize it was done a bibliometric research in national journals A1, A2, B1, B2, B3 and B4 and sociometric analysis, which allows you to check the structure for cooperation between authors and the authors classify according to the regularity and distribution their publications over time. The sample consisted of 54 articles, with 09 on the thematic stakeholders, bioenergy and agro on 13, 17 and 15 on biofuels sustainability. The survey was conducted in the period of 10 years (January 2002-2012). The search keywords were “bioenergy”, “bio”, “biofuel”, “stakeholder”, “stakeholders” and “sustainability”. It was found that about six thematic stakeholders in existing cooperation networks, which involve 21 authors, there is no presence of central actors. Likewise, the themes and agro bioenergy, biofuels and sustainability were found negligible connections between different networks of cooperation. Such information can be concluded that, for now, Brazilian researchers who publish in thematic analysis operate in isolation, without invest and strengthen cooperation among peers and establish leaders who orchestrate followers.